Schedulability analysis and efficient scheduling of rate constrained messages in the TTEthernet protocol. (20th January 2017) - Kermia, Omar
Summary: Over time, cyber‐physical systems are becoming mixed criticality systems. As the complexity and the size of these systems grow, computation/communication resources should be more efficient than with traditional systems. TTEthernet is a communication infrastructure that enables the use of a single physical communication infrastructure for distributed mixed criticality applications while providing timely determinism. TTEthernet distinguishes between two traffic categories: the standard event triggered and the time triggered. The latter, for which higher priority is granted, is subject to strong timing guarantees because of strict periodicity constraint that fixes start‐time cycles of time‐triggered messages. In addition, event‐triggered traffic includes rate‐constrained messages that are of lower priority and have a minimum time interval between their transmission. The paper proposes both an on‐line efficient scheduling algorithm and a necessary and sufficient schedulability condition based on the worst case response time computation for rate‐constrained messages while taking into account time‐triggered messages transmission. Copyright © 2017 John Wiley & Sons, Ltd.